Improving dialogue among researchers, local and indigenous peoples and decision-makers to address issues of climate change in the North - Callaghan, Terry V. (Ambio, 2019)
The Circumpolar North has been changing rapidly within the last decades, and the socioeconomic systems of the Eurasian Arctic and Siberia in particular have displayed the most dramatic changes. Here, anthropogenic drivers of environmental change such as migration and industrialization are added to climate-induced changes in the natural environment such as permafrost thawing and increased frequency of extreme events. Understanding and adapting to both types of changes are important to local and indigenous peoples in the Arctic and for the wider global community due to transboundary connectivity. As local and indigenous peoples, decision-makers and scientists perceive changes and impacts differently and often fail to communicate efficiently to respond to changes adequately, we convened a meeting of the three groups in Salekhard in 2017. The outcomes of the meeting include perceptions of how the three groups each perceive the main issues affecting health and well-being and recommendations for working together better. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13280-019-01277-9) contains supplementary material, which is available to authorized users.